Análise térmica de uma resina composta de nanopartículas: caracterização e envelhecimento - Rogeli Tiburcio Ribeiro da Cunha Peixoto (2008)
The aim of this study was to evaluate the aging of a nanofilled composite resin (Concept Advanced®) during one year. The characterization and evaluation of its homogeneity in commercial syringe was made by Thermogravimetric Analysis (TG/DTG), Differential Scanning Calorimetry (DSC) and Thermomechanical Analysis (TMA). In group 1, 15 analyses throughout syringes were carried without pressing the pestle screw. In groups 2 and 3, the composite resin was all pressed out by the pestle screw and divided in five portions. However, in group 2, throughout the time, the syringes had been kept in the vertical position and group 3 in the horizontal position. In group 4, each sample was obtained every 24 in 24 hours from the central area of each portion during five days. All the analyses of groups 1, 2, 3 and 4 were carried through three syringes in the following times: initial, 6 months and one year. The TG/DTG analyses were carried in not polymerized samples, following a thermal program from 25 to 650ºC, under dynamic air atmosphere. The DSC and the TMA were just carried in group 1, in the initial time, to characterize the material in polymerized samples of 3mm diameter x 1mm thickness per 20 seconds. The curves DSC were obtained following the thermal program from room temperature to 250°C under a nitrogen flow. The TMA was carried under a nitrogen atmosphere from room temperature to 150°C. The curves of TG/DTG showed similar patterns of decomposition in three stages, in all groups independent of the storage time, with similar percentages of loss of mass. Also the weight fraction of inorganic fillers was around 71.5%, showing homogeneity of distribution throughout the syringes. The continuous pressure determined significant alteration in the thermal stability (p< 0,05). The DSC curves showed a glass transition ranged between 94 and 105ºC and eventually an exotherm event at ~160ºC. The TMA showed that the values of the linear coefficient of thermal expansion had varied inside of the same syringe.